Dialogue médecins/entraîneurs autour d`une plateforme de forces. Le comportement postural du tireur - Dudde, R.; Müller, G.; Bourdeaux, O.; Gagey, B.; Weber, B.; Gagey, P.M. (Science & Sports, 2016)
The indoor rifle shooting coaches know they are unable to provide specific criteria to the shooters that allow them to determine precisely the moment they need to press the trigger. They only know that they must anticipate the moment when the crosshairs crosses the center of the target. The possibility, new, of monitoring simultaneously at the time of shooting, the movements of the center of gravity of the shooter and his line of sight explains this failure by showing the independence of the movements of the rifle and of the body. So, a new line of work is open to these shooters: when firing they have to avoid that the weapon moves relative to the body, and on the contrary, they have to ensure that the weapon moves with the body.